873. Clusters of Postpartum Group A Streptococcus (GAS) Infections on a Labor and Delivery (L&D) Unit June-October 2019. (31st December 2020) - Haden, Michael; Liscynesky, Christina; Colburn, Nora; Smyer, Justin; Gonsenhauser, Iahn; Malcolm, Kimberly; Isley, Michelle M; Hardgrow, Michele; Pancholi, Preeti; Thomas, Keelie E; Cygnor, Anita; Tabor, Heather; et al.
Abstract: Background: GAS can cause severe postpartum infections and may be transmitted from colonized healthcare workers (HCWs). Methods: Two cases of GAS bacteremia following vaginal delivery were identified on the L&D unit June-July 2019 (Cluster 1), prompting a carrier-disseminator investigation. Two additional cases were identified September-October 2019 (Cluster 2), followed by an additional 3 cases late October 2019, all of whom delivered on the same night (Cluster 3). All patients and HCWs were evaluated for GAS risk factors and screened for colonization via throat, vaginal and perirectal cultures. During Clusters 1 and 2, only HCWs with patient contact were screened, but this was expanded to the entire unit in October after Cluster 3 was identified. All GAS colonized HCWs were provided chemoprophylaxis and rescreened 7-10 days after treatment to ensure eradication. GAS isolates from patients and HCWs were analyzed by whole genome sequencing (WGS). Results: During Cluster 1 a total of 43 HCWs were screened and HCWA was colonized at all three sites. In Cluster 2, nine HCWs were screened; HCWA was negative at that time but HCWB was colonized in the throat only. Patient 3 was confirmed to be community acquired by pulsed-field gel electrophoresis, patient 4 was closely related by WGS. A new policy was instituted that required all HCWs present at delivery to wear gowns, gloves, masks, eye protection, and to undergo infection prevention education and practice review. Following Cluster 3, all HCWs on the unit were screened (681 total). HCWA was again positive at all 3 sites and two additional HCWs were found to be colonized with the outbreak strain on throat swab only. Isolates from patients 1, 2, 4, 5, 6, 7 and the 4 HCWs were identified as subtype emm 28 and all closely related by WGS (figure 1). A household contact of HCWA was colonized with the outbreak strain as well. Figure 1 Conclusion: A carrier-disseminator investigation identified clusters of nosocomial postpartum GAS infections involving 6 patients, 4 HCWs and a HCW household contact that were highly related based on WGS. The outbreak strain of GAS was likely spread amongst HCWs via ping pong transmission on the unit. Transmission to patients was halted with implementation of strict infection prevention measures and mass screening and chemoprophylaxis of all colonized HCWs. Disclosures: All Authors : No reported disclosures